Leadership in the shadows: exploring the relationship between CEOs' implicit motives and employee satisfaction through social media posts and glassdoor ratings - Lim, Yuan Qi (Nanyang Technological University, 2023)
In the complex world of corporate leadership, the implicit motives of Chief Executive Officers (CEOs) have far-reaching influence that extends beyond the boardroom. Implicit motives are unconscious motivational dispositions that compel an individual to act the way they do. Over the years, motivation researchers have studied the relationships and mechanisms between implicit motives and effective leadership. For our research, we were particularly interested in exploring the influence of CEOs’ implicit motives on their employees. In this study, we examined how the power motive (nPow) and activity inhibition (AI) interact and influence overall employee satisfaction. We also did an exploratory analysis with the affiliation motive (nAff). This study employed a unique approach of utilising online platforms, X (formerly Twitter) and Glassdoor, to measure implicit motives and employee satisfaction respectively. Our findings revealed that both nPow and nAff have a positive influence on overall employee satisfaction. While we failed to find any significant main effect of AI or the interaction effect of nPow and AI on employee satisfaction, this area of study remains of utmost importance in understanding the intricacies of the organisational dynamics. Limitations, implications and directions for future research were discussed.